Hospitalization for pulmonary embolism associated with antecedent testosterone or estrogen therapy in patients found to have familial and acquired thrombophilia. Issue 1 (December 2016) - Prince, Marloe; Glueck, Charles; Shah, Parth; Kumar, Ashwin; Goldenberg, Michael; Rothschild, Matan; Motayar, Nasim; Jetty, Vybhav; Lee, Kevin; Wang, Ping
Abstract Background In patients hospitalized over a 4 year period for pulmonary embolism (PE), we assessed relationships of testosterone (TT) and estrogen therapy (ET) anteceding PE in patients found to have familial-acquired thrombophilia. Methods From 2011 through 2014, 347 patients were hospitalized in Cincinnati Mercy Hospitals with PE. Retrospective chart review was used to identify patients receiving TT or ET before PE; coagulation studies were done prospectively if necessary. Results Preceding hospitalization for PE, 8 of 154 men (5 %) used TT, and 24 of 193 women (12 %) used ET. The median number of months from the initiation of TT or ET to development of PE was 7 months in men and 18 months in women. Of the 6 men having coagulation measures, all had ≥ 1 thrombophilia, and of the 18 women having measures of coagulation, 16 had ≥ 1 thrombophilia. The sensitivity of a previous history of thrombosis to predict PE was low, 25 % (2/8 men), 4 % (1/24 women). Conclusions Of 154 men hospitalized for PE, 8 (5 %) used TT, and of 193 women, 24 (12 %) used ET. Our data suggests that PE is an important complication of TT in men and ET in women, in part reflecting an interaction between familial and acquired thrombophilia and exogenous hormone use.